How Customer Value and Customer Experience Drive Customer Loyalty: The Mediating Role of Customer Satisfaction in Retail Pharmacies - Ermawardani, Kadek Ayu Yessy; Indiani, Ni Luh Putu; Setini, Made (ADPEBI International Journal of Business and Social Science, 2026)
The rapid growth of the retail pharmacy industry has intensified competition among pharmacies, particularly in Denpasar City. This competitive environment requires pharmacy managers to implement effective strategies to maintain and enhance customer loyalty. This study aims to examine the influence of customer value and customer experience on customer loyalty, with customer satisfaction acting as a mediating variable. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 130 pharmacy customers in Denpasar City selected through purposive sampling. The measurement instrument used a five-point Likert scale, and the data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that customer value has a positive and significant effect on both customer satisfaction and customer loyalty. Customer experience has a positive and significant effect on customer satisfaction but does not directly influence customer loyalty. Furthermore, customer satisfaction significantly affects customer loyalty and acts as a mediating variable in the relationship between customer value, customer experience, and customer loyalty. Customer satisfaction partially mediates the relationship between customer value and customer loyalty, while it fully mediates the relationship between customer experience and customer loyalty. These findings indicate that improving customer loyalty in retail pharmacies can be achieved by enhancing perceived customer value and delivering positive customer experiences that ultimately increase customer satisfaction